ATEŞ VE HİPERTERMİNİN İNFANT RAT MODELİNDEKİ OLASI SEREBRAL ETKİLERİ VE İLAÇLARIN BU HASARDAKİ YERİNİN ARAŞTIRILMASI - GİRGİN, FEYZA İNCEKÖY (Fırat Üniveristesi, 2006)
[Abstract Not Available]
Probable cerebral effects of fever and hyperthermia in infant rat model and investigation of plays of medicines in this damage
Keywords: Çocuk Sağlığı ve Hastalıkları